Modernisasi Dayah Salafi Berbasis Total Quality Manajemen - Muhammad Rizal; Muhammad Osama; Saiful Bahri (Indonesian Journal of Islamic Religious Education, 2025)
Competition in educational quality encourages institutions to continuously improve their management standards. One such example is Dayah MUDI Samalanga Bireuen, which implements specific strategies in educational management. This study aims to analyze the strategies employed by Dayah MUDI to enhance the quality of education through the implementation of Total Quality Management (TQM). The study adopts a qualitative approach using a case study method. Data were collected through observation, interviews, and documentation, while data analysis was conducted interactively through data reduction, presentation, and conclusion drawing. The findings indicate that the implementation of TQM at Dayah MUDI is effective in improving educational quality. The strategies applied include training teachers to become professional educators at both local and international levels, hiring specialized instructors for language teaching, and integrating the national Pesantren curriculum. Additionally, Dayah MUDI actively gathers feedback from students and parents as part of its continuous improvement efforts. The institution also provides adequate facilities to support students' development of both soft and hard skills. These findings suggest that the management model adopted by Dayah MUDI can serve as a best practice example for similar educational institutions seeking to improve quality through the application of total quality management principles.